Isolation and 3D Collagen Sandwich Culture of Primary Mouse Hepatocytes to Study the Role of Cytoskeleton in Bile Canalicular Formation In Vitro - Korelova, Katerina; Jirouskova, Marketa; Sarnova, Lenka; Gregor, Martin (Journal of visualized experiments, 2019)
Hepatocytes are the central cells of the liver responsible for its metabolic function. As such, they form a uniquely polarized epithelium, in which two or more hepatocytes contribute apical membranes to form a bile canalicular network through which bile is secreted. Hepatocyte polarization is essential for correct canalicular formation and depends on interactions between the hepatocyte cytoskeleton, cell-cell contacts, and the extracellular matrix. In vitro studies of hepatocyte cytoskeleton involvement in canaliculi formation and its response to pathological situations are handicapped by the lack of cell culture, which would closely resemble the canaliculi network structure in vivo. Described here is a protocol for the isolation of mouse hepatocytes from the adult mouse liver using a modified collagenase perfusion technique. Also described is the production of culture in a 3D collagen sandwich setting, which is used for immunolabeling of cytoskeletal components to study bile canalicular formation and its response to treatments in vitro. It is shown that hepatocyte 3D collagen sandwich cultures respond to treatments with toxins (ethanol) or actin cytoskeleton altering drugs (e.g., blebbistatin) and serve as a valuable tool for in vitro studies of bile canaliculi formation and function.
Keywords: hepatocyty; Animals; Cytoskeleton; biologický transport; mikrofilamenta; mikrotubuly; Bile; cytoskelet; Collagen; Bile Canaliculi; kolagen; Mice; kultivované buňky; myši; extracelulární matrix; Hepatocytes; Biological Transport; Cells, Cultured; žluč; aktiny; Actins; žlučové kanálky; Extracellular Matrix; Microtubules; zvířata; buněčná membrána; Actin Cytoskeleton; Cell Membrane